Cyber forensics : from data to digital evidence - Marcella, Albert J.; Guillossou, Frederic, 1970- (Hoboken, New Jersey : Wiley, 2012)
'An explanation of the basic principles of data. This book explains the basic principles of data as building blocks of electronic evidential matter, which are used in a cyber forensics investigations. The entire text is written with no reference to a particular operation system or environment, thus it is applicable to all work environments, cyber investigation scenarios, and technologies. The text is written in a step-by-step manner, beginning with the elementary building blocks of data progressing upwards to the representation and storage of information. It inlcudes practical examples and illustrations throughout to guide the reader'--
Includes bibliographical references and index.
Keywords: Forensic sciences -- Technological innovations; Electronic evidence; Evidence, Criminal; Criminal investigation; Computer crimes -- Investigation; BUSINESS & ECONOMICS / Accounting / General